PERSEPSI MASYARAKAT TERHADAP PESANTREN : STUDI FENOMENOLOGI - Najah, Faizun (JURNAL ISLAM NUSANTARA, 2021)
This study aims to understand and analyze people's perceptions of the existence of Pondok Pesantren Tarbiyatul Muallimien al-Islamiyah (TMI) Al-Amien Prenduan, Sumenep, Madura. This research uses a qualitative approach to the type of case study. Data collection techniques are carried out through interviews, observation, and documentation. Data analysis was carried out through display data, data reduction, and concluding. The results showed that the community had a positive perception of the existence of the Pondok Pesantren Tarbiyatul Muallimien al-Islamiyah (TMI) Al-Amien Prenduan. The community provides a good and positive label and image for the boarding school with the attitude of the pesantren which has high disciplinary values, educators who care about their students, are ready for use in society, and students who have multi-competence and talent, so that the pesantren is in great demand by the surrounding community as the institution of choice for their sons and daughters.